2016
DOI: 10.1002/open.201600103
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Measurement of Epigenetic DNA Modifications: A Non‐Invasive Assessment of the Whole‐Body Epigenetic Status in Healthy Subjects and Colorectal Cancer Patients

Abstract: Active mechanism of DNA demethylation can be responsible for the activation of previously silenced genes. Products of 5‐methylcytosine oxidation are released into the bloodstream and eventually excreted with urine. Therefore, whole‐body epigenetic status can be assessed non‐invasively on the basis of the urinary excretion of a broad spectrum of epigenetic modifications: 5‐hydroxymethylcytosine (5‐hmCyt), 5‐formylcytosine (5‐fCyt), 5‐carboxycytosine (5‐caCyt), and 5‐hydroxymethyluracil (5‐hmUra). We have develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…With this approach, hydrolyzed DNA samples (hydrolysates) are spiked with a mixture of isotope internal standards to enrich the samples . Using chromatographic separation methods, this approach has been used to quantify all the intermediate products of DNA demethylation pathway in the form of deoxynucleosides in various samples .…”
Section: Methods Of Detection and Quantification Of 5mc And Its Derivmentioning
confidence: 99%
See 3 more Smart Citations
“…With this approach, hydrolyzed DNA samples (hydrolysates) are spiked with a mixture of isotope internal standards to enrich the samples . Using chromatographic separation methods, this approach has been used to quantify all the intermediate products of DNA demethylation pathway in the form of deoxynucleosides in various samples .…”
Section: Methods Of Detection and Quantification Of 5mc And Its Derivmentioning
confidence: 99%
“…Using chromatographic separation methods, this approach has been used to quantify all the intermediate products of DNA demethylation pathway in the form of deoxynucleosides in various samples . This method is effective in distinguishing 5‐methyl‐2′‐deoxycytidine, 5‐(hydroxymethyl)‐2′‐deoxycytidine, 5‐formyl‐2′‐deoxycytidine and 5‐carboxy‐2′‐deoxycytidine as well as 5‐(hydroxymethyl)‐2′‐deoxyuridine using automated isotope‐dilution online two‐dimensional ultra high performance liquid chromatography with tandem mass spectrometry . This approach also helps to reliably identify and quantitate base modifications in DNA and RNA .…”
Section: Methods Of Detection and Quantification Of 5mc And Its Derivmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic mutations are one of the principal factors involved in tumor occurrence and may lead to the activation of proto-oncogenes or the loss of tumor suppressor genes. Furthermore, accumulating evidence demonstrated that genetic modifications are associated with tumorigenesis (8)(9)(10)(11). DNA methylation is a mechanism underlying epigenetic modifications, and is able to affect the DNA conformation, the chromatin structure and the stability of DNA, altering the interactions between DNA and proteins regulating gene expression (12).…”
Section: Introductionmentioning
confidence: 99%